POETICS AND ARTISTIC-AESTHETIC FUNCTION OF PRAISE POEMS (Scientific journal of the Fergana State University, 2024)
In the article, under the influence of praise poems and folklore in written literature, children, children's poetry, the contract poetics of praise poems, the manifestation of children's inner world, worldview and childish thoughts, poetic features, educational, artistic and aesthetic. The acquisition of essence has been studied. The analysis was carried out based on the praise poems of Gafur Ghulam, Tursunboy Adshboyev, Hamza Imonberdiyev, Abdurahman Akbar and Dilshad Rajab. In the creation of literary praises, followership and originality, stylistic skills and individuality of the creator are compared.